Dampak dan Pencegahan Kecanduan Game Online Bagi Generasi Z di Kota Cimahi - Ageng Kanda Saepudin S; Diana Feriska Putri (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Generation Z, often known as Gen Z, is a term used to refer to a group of people who grew up in the digital era, where technology has become an important part of their lives, especially regarding online games that are viral to this day, especially among young people or Gen Z, Playing online games is an activity that has become a trend among Generation Z. The internet offers a lot of convenience and comfort to human civilization. This can at least be seen in the digital economy, artificial intelligence, big data, robotics, and so on. However, the internet can also have negative impacts if it is not used properly. One of them is online games for Gen Z. Technological developments as well as the rampant presence of online games have played an important role in shaping their perception of body image. The city of Cimahi, as an example of a developing environment, provides an interesting conflict or context for understanding how online games influence psychologists' self-perceptions and negative attitudes. This research uses an exploratory qualitative method with a phenomenological theory approach. This theory is used to gain an understanding of how subjects understand and perceive the world around them. The aim of this research is to find out how Generation Z or individuals aged 12-28 years in Cimahi City respond to the impact of online games on self-perception and mental and negative attitudes. The results of this research show that the use of online game application-based entertainment as a whole influences Gen Z's self-insight in terms of self-perception and their courage and influences their mentality. Based on in-depth interviews with 30 subjects in Cimahi City who met the criteria, it was stated that some people experience feelings of insecurity and are easily emotional and emotionally unstable and can even affect their mental health at high levels such as depression. As a result, this research provides more understanding about how to balance yourself so as not to become addicted to online games in Cimahi City.